Respuesta :

Answer:

( x + 2 )² + ( y - 4 )² = 36

Step-by-step explanation:

Standard equation of a circle - ( x - h )² + ( y - k )² = r²

where r = radius and center is at ( h , k )

The given center is ( -2 , 4 )

Thus h = -2 and k = 4

and the given radius is 6

Thus, r = 6

that being said, we plug in the given values into the standard equation

( x - ( - 2 )² + ( y - 4 )² = 6²

Finally we simplify

In - ( -2 ) the two negative signs cancel out and it turns into + 2

6² = 36

The final equation of the circle is ( x + 2 )² + ( y - 4 )² = 36

ACCESS MORE